1985
DOI: 10.4049/jimmunol.135.4.2865
|View full text |Cite
|
Sign up to set email alerts
|

In vivo administration of purified human interleukin 2. II. Half life, immunologic effects, and expansion of peripheral lymphoid cells in vivo with recombinant IL 2.

Abstract: Purified recombinant human interleukin 2 (RIL 2) derived from E. coli containing the inserted gene encoding for IL 2 was administered to 20 patients with a variety of malignancies. Toxicity was dose related and included fever, chills, malaise, arthralgias, myalgias, and unexpectedly, weight gain related to marked fluid retention. All patients receiving more than 10(5) U/kg total cumulative dose developed evidence of fluid retention, and all patients requiring discontinuance of RIL 2 (11/20) received total dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[17][18][19] Furthermore, the observed lymphopenia and subsequent lymphocytosis are consistent with the known characteristics of IL-2 and BEMPEG. 14,15,[17][18][19][20][21] Although the dose of BEMPEG chosen for PIVOT IO 001 did not show single-agent antitumor activity, it was well-tolerated and associated with immune response in previous phase I and phase II studies. 14 Additional biomarker analyses are ongoing to further elucidate any potential mechanisms underlying the lack of added efficacy for BEMPEG plus NIVO versus NIVO monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Furthermore, the observed lymphopenia and subsequent lymphocytosis are consistent with the known characteristics of IL-2 and BEMPEG. 14,15,[17][18][19][20][21] Although the dose of BEMPEG chosen for PIVOT IO 001 did not show single-agent antitumor activity, it was well-tolerated and associated with immune response in previous phase I and phase II studies. 14 Additional biomarker analyses are ongoing to further elucidate any potential mechanisms underlying the lack of added efficacy for BEMPEG plus NIVO versus NIVO monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell surface engineering provides researchers with a toolbox for manipulating individual target cells without the potential danger of disrupting the whole‐body system or metabolism and behavior of bystander cells ( Figure a). [ 160,161 ]…”
Section: Demonstrated Applicationsmentioning
confidence: 99%
“…Singlecell surface engineering provides researchers with a toolbox for manipulating individual target cells without the potential danger of disrupting the whole-body system or metabolism and behavior of bystander cells (Figure 8a). [160,161] Drug-loaded lipid NPs have been conjugated to the surface of T cells, to stimulate the cells in a pseudo-autocrine manner. [37] The conjugation was achieved by the TMMA reaction between the cell-surface thiols and maleimide-bearing lipid NPs.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Of note, such mAbs would not only change the receptor specificity of endogenously or exogenously applied IL-2 but may also significantly prolong the half-life of the otherwise short-lived IL-2 (T 1/2 only 6-7 min) [42,43] with renal elimination accounting for 75% of IL-2 clearance [44]. The first experimental studies to show such immunomodulatory capacities of injected anti-IL-2 mAbs were conducted by Jonathan Sprent and coworkers [41], and later on by Fred Finkelman and coworkers [43] The Multiple Functions of Interleukin-2 Int Arch Allergy Immunol 2024;185:286-300 DOI: 10.1159/000533677 who demonstrated that murine Treg cells can be selectively expanded by IL-2 complexes (IL-2C) formed upon injection of the rat anti-mouse IL-2 monoclonal antibody JES-6.1A12 (Table 2; Fig.…”
Section: Distinct Monoclonal Antibodies Shape the Function And Increa...mentioning
confidence: 99%